PENGARUH TATA RUANG KANTOR DAN KOMUNIKASI KANTOR TERHADAP SEMANGAT KERJA PEGAWAI DISPERTAN PP KABUPATEN KARANGANYAR - Elva Elviana; Hery Sawiji; Winarno Winarno (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
The purpose of this study isto determine: (1) find out whether there is an effect of office layout on the spirit of the employees in Dinas Pertanian, Pangan dan Perikanan Kabupaten Karanganyar, (2) find out whether there is an effect of office communication on the spirit of the employees in Dinas Pertanian, Pangan dan Perikanan Kabupaten Karanganyar, and (3) determine whether there is an influence between office layout and office communication on the spirit of the employees in Dinas Pertanian, Pangan dan Perikanan Kabupaten Karanganyar.This research is a quantitative research using survey method. The population in this study were employees of the Dinas Pertanian, Pangan dan Perikanan Kabupaten Karanganyar. Sources of data in this study came from respondents and literature study. The sampling technique was done by simple random sampling. Data was collected through interviews, questionnaires and observations. The validity test technique uses Product Moment Correlation, while the reliability test uses Cronbach's alpha. The data analysis technique used multiple regression analysis techniques with the help of SPSS version 25.The results showed that 1) There is a positive and significant effect of office layout on the spirit of the employees. This is evidenced by the tcount of 2,619 > ttable of 1,672, thus Ho is rejected and H1 is accepted. 2) There is a positive and significant effect of office communication on the spirit of the employees. This is evidenced by the tcount of 5,088 > ttable of 1,672, thus Ho is rejected and H2 is accepted. And 3) There is a positive and significant effect of office layout and office communication simultaneously on the spirit of the employees. This is evidenced by Fcount(33.053) > Ftable(3.159) then Ho is rejected and H3 is accepted. Thus, the overall results of this analysis support the proposed hypothesis.